RESPON PADI GOGO (Oryza sativa L.) TERHADAP PEMBERIAN SILIKAT DAN PUPUK FOSFAT PADA TANAH ULTISOL - ZULPUTRA ZULPUTRA; WAWAN WAWAN; NELVIA NELVIA (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2014)
The research aims to study the response of upland rice on the application of silicates and phosphate fertilizer on Ultisol. The study was conducted in land Ultisol in Pematang Berangan Village, Rokan Hulu Regency, Riau Province. Research in the form of experimental factorial completely randomized design consisting of two factors. The first factor is silicate consists of four levels (0, 50, 75, and 100 kg SiO2/ha), while the second factor that phosphate fertilizer consists of four levels (0, 36, 54, and 72 kg P2O5/ha), each combination was repeated three times. The results showed that application of silicates and phosphates increase the growth and yield of upland rice. The application of 100 kg SiO2 and 36 kg P2O5 per hectare increasing of the percentage of grain pithy and weight of dry grain per square meter, about 21% and 117% respectively compared to without silicates and phosphates.